Application of the Fuzzy Sets Theory in the Management of Technological Processes for the Production of Automation Technical Means - Omarov, M.; Bilousov, M.; Starodubtsev, M.; Shybanov, S.; Jabrayilzade, E. (My University, 2025)
It is established that the main problems of algorithmization for the management of technological processes under conditions of uncertainty are the high dimensionality of the task, the need for prompt identification of technological objects of control and the choice of optimal control influences. It is shown that these problems can be solved using fuzzy logic and decision theory. A method for formalizing fuzzy concepts based on an objective probabilistic approach is proposed, which increases the reliability of modeling results. Based on fuzzy logic, a method for identifying multidimensional technological objects has been developed, in which, in order to reduce the dimensionality of the problem, a conjunctive inference rule is used instead of the generally accepted disjunctive one to build a relationship between a multidimensional input and output, which simplifies the inference procedure and leads to a more compact and convenient model for practical application.
Keywords: technological object; fuzzy environment; operational identification; problem dimension